Training Patterns and Mental Health of Bodybuilders and Fitness Athletes During the First Lockdown of the COVID-19 Pandemic—A Cross-Sectional Study - Iff, Samuel; Fröhlich, Stefan; Halioua, Robin; Imboden, Christian; Spörri, Jörg; Scherr, Johannes; Butzke, Ingo; Seifritz, Erich; Claussen, Malte Christian (Frontiers in Sports and Active Living, 2022)
Background: Government restrictions during the first COVID-19 lockdown, such as the closure of gyms and fitness centers, drastically limited the training opportunities of bodybuilders and fitness athletes (BoFA) who rely on indoor training facilities. This provided a unique situation to investigate the effect of training limitations on the training patterns, training adaptive strategies and mental health of BoFAs. Objectives The primary aim of this study was to investigate differences in the training patterns and the mental health of BoFA before and during the first COVID-19 lockdown. The secondary aim was to assess whether BoFA who exhibited features of muscle dysmorphia were affected differently from the group that did not. Methods A cross-sectional study was conducted with 85 BoFAs by means of an online questionnaire asking about sports activity, intensity, subjective physical performance, and economic status, including primary or secondary occupations before (from memory) and during lockdown, current physical health problems and financial fears, symptoms of depression, sleep disorders, anxiety (trait and state), muscle dysmorphia, coping mechanisms and actions during the first lockdown in Switzerland. Results Training patterns and mental health of BoFA were influenced by the COVID-19 pandemic and first lockdown. During lockdown, the physical activity on the BoFA dropped significantly from 2.3 ± 0.8 h per day to 1.6 ± 0.9 h per day (p < 0.001), the subjective training intensity decreased significantly from 85.7 ± 13.2% to 58.3 ± 28.3% (p < 0.001) and the subjective performance declined significantly from 83.4 ± 14.3% to 58.2 ± 27.8% (p < 0.001) of maximal performance. In comparison to those without risk for body dysmorphia, participants at risk rated their maximal performance significantly lower and scored significantly higher for depression, sleep disorders and anxiety. Conclusion This study showed the significant changes on the training patterns of BoFA before and during the first COVID-19 lockdown and poor mental health scores of BoFA during the lockdown itself, with those at risk of muscle dysmorphia scoring statistically worse regarding mental health than those with no risk of muscle dysmorphia. To better understand the particularities of BoFA, further investigation is needed to understand their psychology and in particular the effect of training restrictions on it.